(untitled) (Research, Society and Development, 2020)
This article aims to highlight, by means of a systematic literature review, the main research focuses arising from the methodological strategy related to the production of videos by students of Basic Education, in their different levels of teaching and/or disciplines, so that we can reflect on the possible contributions to the teaching and learning processes. Using the Sucupira Platform as a database, exclusively national journals in ​​Education of strata A1, A2 and B1 were considered, in the corresponding period between 2014 and 2019. In order to deepen this theme, this systematic literature review was based on Kichenham’s proposal and subsequent content analysis according to Bardin’s proposal. The panorama of research found points to the scarcity of works related to the production of videos by students, in addition to suggesting resistance and lack of training on the part of teachers in using digital technologies in the classroom. However, all selected researches contemplate positive results regarding the protagonism and involvement of students, autonomy, motivation and, above all, the construction of knowledge.